2019
DOI: 10.1111/nmo.13530
|View full text |Cite
|
Sign up to set email alerts
|

24‐hour monitoring of transient lower esophageal sphincter relaxation events by long‐term high‐resolution impedance manometry in normal volunteers: The “mirror phenomenon”

Abstract: Background The aim of this study was to investigate the frequency and circadian changes in transient lower esophageal sphincter relaxations (TLESRs) in normal volunteers using 24‐hour high‐resolution impedance manometry (HRIM). Methods Fifteen volunteers underwent HRIM. TLESRs were recorded during the mealtime, 2‐hour postprandial, daytime, and supine periods. The catheter was firmly secured to the nose, and subjects went home, ate normal meals, and continued routine daily activities. Key Results Successful re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Two previous ambulatory studies in GERD subjects 7,8 utilized outdated perfused sleeve manometry. The current prolonged ambulant study of the mechanisms associated with GER in GERD subjects took advantage of the new HRM technology combined with pH impedance that has been utilized in healthy volunteers to study TLESR over a 24‐h period 27 . The present study confirmed that TLESR is unequivocally the dominant mechanism associated with GER.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Two previous ambulatory studies in GERD subjects 7,8 utilized outdated perfused sleeve manometry. The current prolonged ambulant study of the mechanisms associated with GER in GERD subjects took advantage of the new HRM technology combined with pH impedance that has been utilized in healthy volunteers to study TLESR over a 24‐h period 27 . The present study confirmed that TLESR is unequivocally the dominant mechanism associated with GER.…”
Section: Discussionsupporting
confidence: 74%
“…TLESR with GER [group A 18.0 (9-42) and group B 24.0(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), p = 0.06]. However, post-prandial TLESR with GER were more common in group B [17.0 (9-24)] than group A[13.5 (7-34), p = 0.014].During post-prandial exercise, group B had significantly more TLESRs with GER [8.0 (4-14)] than group A [6.0 (3-19), p = 0.007].…”
mentioning
confidence: 99%
“…However, our data suggest that maintaining rest LES tone may not be essential for preventing reflux, as almost 70% of the reflux episodes we observed occurred due to TLESR. Although TLESR may be a normal physiological motor event in healthy subjects [12], previous studies have proven that TLESR plays a crucial role in the occurrence of gastroesophageal reflux disease [13]. It appears that the major mechanisms of reflux in our cohort of patients recovering from critical illness and receiving minimal sedation are similar to non-ventilated patients.…”
Section: Discussionmentioning
confidence: 64%
“…It appears that the major mechanisms of reflux in our cohort of patients recovering from critical illness and receiving minimal sedation are similar to non-ventilated patients. By contrast, a notable feature of esophageal activity that often preceded TLESR was panesophageal secondary peristalsis, an abnormality never seen in healthy subjects [12]. It remains unclear, whether this secondary peristalsis is itself a trigger of TLESR.…”
Section: Discussionmentioning
confidence: 92%
“…Meanwhile, the role of HRM in human medicine is expanding. Emerging applications in humans include the implementation of three-dimensional (3-D) HRM, in which there is a 9-cm segment lined with 12 pressure sensing loci and 8 radially dispersed pressure sensors at each locus, to evaluate pressure distributions at the pharynx, UES, and EGJ (249) or combination HRM-impedance technology to evaluate post-prandial TLESRs (250) or belching disorders (247). HRMimpedance technology is also being trialed in humans to assess bolus transit and post-residue swallows in patients with oropharyngeal (251) and esophageal dysmotility (252,253).…”
Section: Future Directions In Veterinary Medicinementioning
confidence: 99%